The marks of inequality in black women with breast cancer in Brazil: : a theoretical study (Revista Brasileira Multidisciplinar, 2026)
Abstract:Black women's access to breast cancer treatment highlights significant inequalities in the health system, related to racial discrimination, socioeconomic barriers, and lack of information. In this context, health education strategies are essential to promote more inclusive care and reduce these disparities. Thus, this study seeks to understand the importance of discussions on ethnic-racial relations in Brazil, focusing on black women and the conditions that involve their access to treatment and prevention of breast cancer. This is a bibliographic, theoretical, and documentary investigation of a qualitative nature, focusing on classic works that discuss the socio-historical formation of Brazil. As a result, it was found that racial inequality understood from the reinterpretation of the socio-historical formation of Brazil, is one of the major barriers for black women to access treatment for breast cancer, in which determinants of gender, race, and class are combined that impact the realization of the right to health. Therefore, it is important and urgent to expand specific public policies aimed at this population in oncological care, which consider the need for actions to combat the effects of racism and racial discrimination. Such policies must be integrated with studies and research that address the health of black women and oncological care in a specific way.
Keywords: black population; black women; breast neoplasms; gender health.